Nails Analysis for Drugs Used in the Context of Chemsex: A Pilot Study*. Issue 1 (11th March 2019) - Busardò, Francesco Paolo; Gottardi, Massimo; Pacifici, Roberta; Varì, Maria Rosaria; Tini, Anastasio; Volpe, Anna Rita; Giorgetti, Raffaele; Pichini, Simona
Abstract: Nail analysis can be performed as a substitute or complement to hair analysis for the retrospective determination of psychotropic drugs consumption in forensic contexts. The application of nail analysis in a "chemsex" context is reported herein. An ultra-performance liquid chromatography–tandem mass spectrometry method was developed to quantify the most common drugs of abuse, synthetic cannabinoids, synthetic cathinones and GHB in fingernails and toenails of individuals presumptively using these drugs in music and sex settings. Results were compared to the concentrations measured in hair. Nail and hair keratin matrices were digested with VMA-TM3 ® buffer reagent and underwent a solid phase extraction before chromatographic separation with reversed phase columns and a linear gradient elution with 5 mM ammonium formate and acetonitrile, for detecting classic drugs of abuse, or 0.1% formic acid and methanol, for detecting synthetic cathinones, synthetic cannabinoids, and GHB. Analytes were detected with a triple quadrupole mass spectrometer operated in multiple reaction monitoring mode after positive electrospray ionization. Nails of individuals practicing "chemsex" contained at least three different psychoactive drugs, and up to eight drugs simultaneously. Identified drugs included cocaine, benzoylecgonine, cocaethylene, delta-9-tetrahydrocannabinol, amphetamine, methamphetamine, 3, 4-methylenedioxymethamphetamine, 3, 4-methylenedioxyamphetamine, ketamine, norketamine, mephedrone, methylone, 4-methyletcathinone, methcathinone, γ-hydroxybutyric acid (GHB) and γ-butyrolactone. Most used drugs were MDMA and GHB followed by cocaine and ketamine. Drugs concentrations ranged from 0.1 to 690 ng/mg in fingernails. In the two individuals who also provided toenails, concentrations were always higher in fingernails than in toenails, while in two other individuals who donated also hair, concentrations in this latter matrix were either higher or lower than those measured in fingernails. This study demonstrated that nails may well represent an appropriate non-conventional biological matrix to provide additional information in forensic toxicology.